Diagnóstico del nivel de cumplimiento del Reglamento Interno de Seguridad y Salud en el Trabajo del Ministerio de Transporte y Obras Públicas de la ciudad de Loja - Merino Cumbicus, Mery Katherine (2023)
The main objective of this research work, under the title "Diagnosis of the level of compliance with the Internal Occupational Safety and Health Regulations of the Ministry of Transportation and Public Works", was to determine the degree of compliance with the Occupational Safety and Health policy. For this purpose, the process of socialization of the regulation among employees and workers was verified, in addition to evaluating its application in practice in the Ministry. The internal occupational health and safety regulations reflect the organization's commitment to the well-being of its human resources. The internal occupational health and safety regulations reflect the organization's commitment to the well-being of its human resources, demonstrating that the safety and health of its workers are fundamental priorities. This document also contributes to fostering a culture of prevention and shared responsibility, where both employers and employees assume responsibility for complying with the rules and practicing safe habits in their work routine. The correct implementation of these regulations not only protects workers from possible accidents or occupational illnesses, but also has a positive impact on the organization's productivity and efficiency. The research adopted a quantitative approach, a valuable and profound methodological approach that seeks to understand and analyze the social reality from the perspective of the participants involved. In addition to opting for the Pure Chance theory which proposes that all workers in a given set have the same probability of having an accident. It follows that no single pattern of events can be discerned to cause it. According to this theory, all accidents 4 are considered to be included in Heinrich's group of chance events and the non-existence of interventions to prevent them is maintained. (Patel, 2019). The main results showed that 100% of the servers and workers consider of vital importance to have such regulation, since it permits them to know in profound the risks and threats to which they are exposed during their work activities and to know who to turn to in case of any accident. To develop the discussion and establish conclusions and recommendations, the results of the field research, the legal regulations and the theoretical foundations established in the literature review were considered.